Livelihood Resilience of Small Fishers Households in Rural Areas, Indonesia - Nissa', Zulfa Nur Auliatun; Nurmastiti, Ardela; Setyowati, Ratih; Mariyani, Siti (HABITAT, 2023)
The concept of livelihood resilience provides a unique framework for examining the utilization of livelihood capital and resilience values of farming households in ensuring sustainable communities. This study was conducted in Muarareja Village, Tegal Barat Subdistrict, Tegal City, in January-March 2019 by assessing the utilization of five livelihood capitals and livelihood resilience actions of fisher households facing social, economic, and ecological pressures. Data were collected through surveys, observations, and structured interviews, supported by a literature review. Purposive stratified-accidental sampling was used to interview fishermen from every socioeconomic class. The sample was 40 small-scale fisher households divided into 35 lower-layer fisher households and five upper-layer fisher households. Data analysis was conducted descriptively with simple tabulation to describe the condition of the study area. The results showed that social capital is the main capital utilized by lower-layer fishermen. Meanwhile, physical and financial capital are mostly utilized by upper-layer fisher households. Genealogical relationships and territorial ties in the study location make social capital dominant. Self-organization is the highest resilience action by lower-layer fisher households by prioritizing the value of trust. Meanwhile, upper-layer fishermen households have a high resilience value in the capacity of learning action on the value of experimentation. Ownership of larger production capital makes it easier for upper-layer fishermen households to make many alternatives to continue fishing. Meanwhile, due to limited ownership and access to production capital, lower-layer fishing households prioritize the value of trust between neighbors and relatives as their social safety net.